Characterization And Properties Of Thermoplastic Tapioca Starch Based High Density Polyethylene / Natural Rubber Blends - Abd Wahab, Mohamad kahar (2013)
Effects of thermoplastic tapioca starch (TPS) on the properties of HDPE/NR (70/30) blends were investigated. Tapioca starch was chosen to incorporate into HDPE/NR blends due to its abundance and biodegradability properties. However certain drawbacks, such as poor compatibility with the hydrophobic polymer matrix, tendency not to disperse during processing and affinity for moisture are factors which lower the potential of TPS based blends. TPS loadings were varied from 0 wt% to 30 wt% and incorporated into HDPE/NR blends using HAAKE rheomix 600 internal mixer. The melt blending was carried out at temperature of 150 ⁰C with the rotor speed of 50 rpm for 12 minutes. Mechanical properties of blends were evaluated as a function of TPS loadings and the influence of blend’s modification. The tensile strength showed a sharp drop on addition of TPS particle into the blends system due to the inability of TPS to support the stress transfer between phases. Few series of blend’s modification have been done in order to improve the mechanical properties of the blends. TPS was treated with citric acid in order to improve the plasticization and fluidity of TPS in HDPE/NR blends. TPS can be partly depolymerised to produce low viscosity product when processed with citric acid. It is also found that TPS with low molecular weight (Mw) is easy to disperse in the thermoplastic elastomer (TPE) blend and improve wettability at the inter phase of TPS-HDPE/NR as shown by scanning electron microscope (SEM). The effect of polyethylene-grafted-maleic anhydride (PE-g-MA) as a compatibilizer was also xxviii shown to be effective in improving the tensile strength. The degree of TPS adhesion and dispersion in blends were improved in the cases of PE-g-MA compatibilized blends. The improvement in compatibilized TPS-HDPE/NR interface adhesion was clearly indicated in SEM study. In the cases of dynamic vulcanization system, two series were prepared; (a) sulphur vulcanized blends and (b) N, N’-m-phenylenebismaleimide (HVA-2) vulcanized HDPE/NR/TPS blends. Tensile strength, Young’s modulus and elongation at break exhibit significant improvement when HDPE/NR/TPS blends were subjected to the both crosslinkers. Moreover, SEM micrographs showed fine TPS was dispersed and well embedded in vulcanized HDPE/NR matrix. Comparison was also made based on the results of gel content, thermogravimetric analysis(TGA) and differential scanning calorymetry (DSC). Generally, the improvement observed in tensile properties, blends homogeneity and thermal stability can be correlated to the crosslink formation within the NR phase.